gs - h ·ª h ª (tgx)′ = sec 2 x(ctgx)′ = − csc...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: hç ·ª* h ç ª · (tgx)′ = sec 2 x (ctgx)′ = − csc x (sec x)′ = sec x ⋅ tgx (csc x)′ = − csc x ⋅ ctgx 2 (arcsin x)′ = 1 (a x )′ = a x ln a 1 (log a x)′ = x ln a 1− x2 1 (arccos x)′ = − 1− x2 1 (arctgx )′ = 1+ x2 1 (arcctgx)′ = − 1+ x2 ∫ tgxdx = − ln cos x + C ∫ ctgxdx = ln sin x + C ∫ sec xdx = ln sec x + tgx + C ∫ csc xdx = ln csc x − ctgx + C dx 1 x = arctg +C 2 +x a a dx 1 x−a ∫ x 2 − a 2 = 2a ln x + a + C dx 1 a+x ∫ a 2 − x 2 = 2a ln a − x + C dx x ∫ a 2 − x 2 = arcsin a + C ∫ cos ∫ sin dx 2 x x = ∫ sec 2 xdx = tgx + C = ∫ csc 2 xdx = −ctgx + C dx 2 ∫a ∫ sec x ⋅ tgxdx = sec x + C ∫ csc x ⋅ ctgxdx = − csc x + C x ∫ a dx = 2 ax +C ln a ∫ shxdx = chx + C ∫ chxdx = shx + C ∫ dx x ±a 2 2 = ln( x + x 2 ± a 2 ) + C I n = ∫ sin n xdx = ∫ cos n xdx = 0 0 π 2 π 2 n −1 I n −2 n ∫ ∫ ∫ h* ç ª · (j m x2 a2 2 x + a dx = x + a + ln( x + x 2 + a 2 ) + C 2 2 x2 a2 x 2 − a 2 dx = x − a 2 − ln x + x 2 − a 2 + C 2 2 x2 a2 x a 2 − x 2 dx = a − x 2 + arcsin + C 2 2 a 2 2 sin x = 2u 1+ u2 cos x = 1− u2 1+ u2 u = tg x 2 dx = 2du 1+ u2 ( ` E n n n e x − e−x : shx = 2 x e + e−x : chx = 2 shx e x − e − x : thx = = chx e x + e − x lim sin x =1 x →0 x 1 lim(1 + ) x = e = 2.718281828459045... x →∞ x arshx = ln( x + x 2 + 1n archx = ± ln( x + x 2 − 1) 1 1+ x arthx = ln 2 1− x ª Žj·* ( ·( Žj· ª n nA -α 90°-α 90°+α 180°-α 180°+α 270°-α 270°+α 360°-α 360°+α · sin -sinα cosα cosα sinα -sinα -cosα -cosα -sinα sinα { ª · ·j Ž cos cosα sinα -sinα -cosα -cosα -sinα sinα cosα cosα tg -tgα ctgα -ctgα -tgα tgα ctgα -ctgα -tgα tgα ctg -ctgα tgα -tgα -ctgα ctgα tgα -tgα -ctgα ctgα sin(α ± β ) = sin α cos β ± cos α sin β cos(α ± β ) = cos α cos β sin α sin β tg (α ± β ) = tgα ± tgβ 1 tgα ⋅ tgβ ctgα ⋅ ctgβ 1 ctg (α ± β ) = ctgβ ± ctgα α+β α −β cos 2 2 α+β α −β sin α − sin β = 2 cos sin 2 2 α+β α −β cos α + cos β = 2 cos cos 2 2 α+β α−β cos α − cos β = 2 sin sin 2 2 sin α + sin β = 2 sin · ·¨ ªí sin 2α = 2 sin α cos α cos 2α = 2 cos 2 α − 1 = 1 − 2 sin 2 α = cos 2 α − sin 2 α ctg 2α − 1 ctg 2α = 2ctgα 2tgα tg 2α = 1 − tg 2α sin 3α = 3 sin α − 4 sin 3 α cos 3α = 4 cos 3 α − 3 cos α tg 3α = 3tgα − tg 3α 1 − 3tg 2α · ·¨ ªí sin tg α 1 − cosα =± § 2 2 x cos ctg α 1 + cosα =± 2 2 α 1 − cosα 1 − cosα sin α =± = = x 2 1 + cosα sin α 1 + cosα a b c = = = 2R sin A sin B sin C arcsin x = · ¸j Ž ª · α 1 + cosα 1 + cosα sin α =± = = 2 1 − cosα sin α 1 − cosα ·nø í· ª c 2 = a 2 + b 2 − 2ab cos C arctgx = ·a Ø í·* ª π − arccos x 2 π − arcctgx 2 {· m Ÿ ª ——Õ§ = Le ibn i z ¬Ç k (uv) ( n ) = ∑ C n u ( n−k ) v ( k ) k =0 n = u ( n ) v + nu ( n−1) v′ + ž n(n − 1) ( n−2) n(n − 1)(n − k + 1) ( n −k ) ( k ) u v ′′ + + u v + + uv ( n ) 2! k! *ª8‰j · F( x) = x § f (b) − f (a ) = f ′(ξ )(b − a ) f (b) − f (a) f ′(ξ ) = F (b) − F (a ) F ′(ξ ) ª -o·* ª -o· M-o· ª K = 0; a K= ds = 1 + y ′ 2 dx, ∆α .∆α : ∆s K = lim M y ′ = tgα H′ M ; ∆s MM ′ y ′′ ∆α dα = = . ∆s →0 ∆s ds (1 + y ′ 2 ) 3 1 K= . a b−a ( y0 + y1 + + y n−1 ) n b−a 1 [ ( y0 + y n ) + y1 + + y n−1 ] n2 b−a [( y0 + y n ) + 2( y 2 + y 4 + + y n −2 ) + 4( y1 + y3 + + y n−1 )] 3n o ˆ-· ª © ∫ f ( x) ≈ a b b ∫ f ( x) ≈ a b a ∫ f ( x) ≈ W = F ⋅s n n n ª ˆ-o·* n Àl © · F = p⋅ A mm F = k 1 2 2 , kˆ-o· ª r b 1 y= f ( x)dx b−a ∫ a 1 2 ∫ f (t )dt b−a a b 2n ÷· ª Ø d = M 1 M 2 = ( x2 − x1 ) 2 + ( y 2 − y1 ) 2 + ( z 2 − z1 ) 2 AB un ÷· ª Pr ju AB = AB ⋅ cos ϕ ,ϕ xx x x Pr ju ( a1 + a2 ) = Pr ja1 + Pr ja 2 xx x x a ⋅ b = a ⋅ b cosθ = a x bx + a y b y + a z bz , n ÷· ª cosθ = i xxx c = a × b = ax bx ÷ ·* n ª j ay by 2 2 2 , 2 2 2 Ø a x bx + a y b y + a z bz a x + a y + a z ⋅ bx + b y + bz k x xx a z , c = a ⋅ b sin θ÷ ·* .n ª bz ay by cy xxx v = w× r. az xxx bz = a × b ⋅ c cosα ,αn ÷· ª cz ax x xx xxx [ a b c ] = ( a × b ) ⋅ c = bx cx Ø š ª ÷n·* 1÷n· ª 2÷n·* ª 3÷n·* ª Ø š A( x − x0 ) + B( y − y 0 ) + C ( z − z 0 ) = 0 Ax + By + Cz + D = 0 xyz + + =1 abc ª ÷n· d= x n = { A, B, C}, M 0 ( x0 , y0 , z 0 ) Ax0 + By0 + Cz 0 + D A2 + B 2 + C 2 x s = {m, n, p}; ÷n· ª x = x0 + mt y = y 0 + nt z = z + pt 0 ª ÷n·* ª ÷n· 1÷n· ª 2÷n· ª 3÷n· ª ª ÷n·* ª ÷n·* x − x0 y − y 0 z − z 0 = = = t, m n p x2 y2 z 2 + + =1 a2 b2 c2 x2 y2 + = z , p, q 2 p 2q x2 y2 z2 + − =1 a2 b2 c2 x2 y2 z2 − + =÷n·1 ª a2 b2 c2 h 9 dz = È È ¡ ∂z ∂z dx + dy ∂x ∂y du = ∂u ∂u ∂u dx + dy + dz ∂x ∂y ∂z ∆z ≈ dz = f x ( x, y ) ∆x + f y ( x, y )∆y dz ∂z ∂u ∂z ∂v = ⋅+⋅ dt ∂u ∂t ∂v ∂t ∂z ∂z ∂u ∂z ∂v z = f [u ( x, y ), v ( x, y )] = ⋅+⋅ ∂x ∂u ∂x ∂v ∂x u = u ( x, y ) v = v ( x, y ) ∂u ∂u ∂v ∂v du = dx + dy dv = dx + dy ∂x ∂y ∂x ∂y z = f [u (t ), v(t )] È F ( x, y ) = 0 F ( x, y , z ) = 0 F dy =− x dx Fy F ∂z =− x ∂x Fz F d2y ∂ = (− x ) 2 dx ∂x Fy Fy ∂z =− ∂y Fz ∂F ∂v = Fu ∂G Gu ∂v Fv Gv F dy ∂ (− x ) ⋅ ∂y Fy dx Fq* ∪ ª · F ( x, y , u , v ) = 0 G ( x, y, u, v) = 0 ∂v ∂x ∂v ∂y ∂u 1 ∂( F , G) =− ⋅ ∂x J ∂ ( x, v ) ∂u 1 ∂( F , G) =− ⋅ ∂y J ∂ ( y, v ) ðm – ∂F ∂ ( F , G ) ∂u J= = ∂G ∂ (u , v) ∂u 1 ∂( F , G ) =− ⋅ J ∂ (u , x) 1 ∂( F , G ) =− ⋅ J ∂ (u , y ) x = ϕ (t ) y = ψ (t ) z = ω (t ) M∪ Fq* ª · È F ( x, y , z ) = 0 È1 È2 ¡ È3 ¡ Aq ξ·* ª M ( x0 , y 0 , z 0 )∪ Fq* ª · x − x0 y − y 0 z − z 0 = = ϕ ′(t 0 ) ψ ′(t 0 ) ω ′(t 0 ) ϕ ′(t 0 )( x − x0 ) + ψ ′(t 0 )( y − y0 ) + ω ′(t 0 )( z − z 0 ) = 0 F ( x, y , z ) = 0 , G ( x, y , z ) = 0 M ( x0 , y 0 , z 0 ) n = {Fx ( x0 , y0 , z 0 ), Fy ( x0 , y 0 , z 0 ), Fz ( x0 , y0 , z 0 )} Fx ( x0 , y0 , z 0 )( x − x0 ) + Fy ( x0 , y 0 , z 0 )( y − y 0 ) + Fz ( x0 , y 0 , z 0 )( z − z 0 ) = 0 x − x0 y − y0 z − z0 = = Fx ( x0 , y0 , z 0 ) Fy ( x0 , y 0 , z 0 ) Fz ( x0 , y 0 , z 0 ) T ={ Fy Gy Fz Fz , G z Gz Fx Fx , G x Gx Fy } Gy z = f ( x, y ) p ( x, y )ˆ· ²ª r l p ( x, y ) lˆ·* ²ª r ∂f ∂f ∂f = cosϕ + sin ϕ ∂l ∂x ∂y ∂f ∂f i+ j ∂x ∂y e = cosϕ ⋅ i + sin ϕ ⋅ j l ϕx z = f ( x, y ) { ˆ· ²ª r ∴ @l ¢ · gradf ( x, y ) = ∂f = grad f ( x, y ) ⋅ e ∂l ∂f ∂l gradf ( x, y ) lˆ· ²ª r f x ( x0 , y 0 ) = f y ( x0 , y 0 ) = 0 A < 0, ( x0 , y0 ) 2 AC − B > 0 A > 0, ( x0 , y0 ) 2 AC − B {< 0 AC − B 2 = 0{ , ³ · Hrª * f xx ( x0 , y0 ) = A, f xy ( x0 , y0 ) = B, f yy ( x0 , y0 ) = C ² · ˆrª ² · ˆrª ² · ˆrª · 8³rª * 1− qn 1+ q + q ++ q = 1− q (n + 1)n 1+ 2 + 3 ++ n = 2 11 1 1+ + + + x 23 n 2 n −1 1 2ˆ²rª ·* 3ˆ²rª · —{— * ρ < · 1ˆ²rª ρ = lim n u n ρ > · 1ˆ²rª * n →∞ ρ = · 1ˆ²rª * ρ < · 1ˆ²rª U n +1 ρ = lim ρ > · 1ˆ²rª * n →∞ U n ρ = · 1ˆ²rª sn = u1 + u 2 + + u n ; lim sn { n →∞ u1 − u 2 + u3 − u 4 + ( H ·* n ‘ª X } − u1 +u 2 −u3 + , u n > 0) s ≤ u1 , — —‘ ·* n ª rn rn ≤ u n+1 u n ≥ u n+1 0 lim u} = 0 n →∞ n u nΗ n ‘·* ª nΗ ª ‘· (1)Η n ‘·* ª (−1) n ∑n (1)u1 + u 2 + + u n + (2) (2) nΗ ª ‘· nΗ ª ‘· p (2) u1 + u 2 + u3 + + u n + 0(1) } (1)Η n ‘· ª 1 ∑n 1 ∑ n2 ∑n 2 3 1 p ≤ p >1 1 1− x ª Hn·* x RHn·* ª 1 ρ 1 + x + x + x + + x + x n x < 1Hn· ª x ≥ 1x x 0 } (3)a0 + a1 xx a2 x 2 + + an x n +} + 0 x < Rx x Rx x > Rx x = Rx ρ ≠ 0x 0 } lim a n+1 = ρx n →∞ a n anx a n+1x (3)Hn· ª R= ρ = 0x R = +∞ ρ = +∞x R=0 È 0 } n x0 0 0 = } h | l f ( x ) = f ( x0 )( x − x0 ) + f ( n+1) (ξ ) Rn = ( x − x0 ) n+1 , f 0 x) ( } (n + 1)! f ′′( x0 ) f ( n ) ( x0 ) ( x − x0 ) 2 + + ( x − x0 ) n + 2! n! n ‘ H·* ª lim Rn = 0 n →∞ f ( x) = f (0) + f ′(0) x + f ′′(0) 2 f ( n ) (0) n x ++ x + 2! n! m(m − 1) 2 m(m − 1)(m − n + 1) n x ++ x + x 2! n! x3 x5 x 2 n−1 sin x = x − + − + (−1) n−1 + x (− < x < +∞) ∞ 3! 5! (2n − 1)! (1 + x ) m = 1 + mx + ª ø.o· (−1 < x < 1) e ix = cos x + i sin xx e ix + e − ix cos x = 2 ix −ix sin x = e − e 2 ³ Èr· ª f (t ) = A0 + ∑ An sin( nωt + ϕ n ) = x x ÷ ¸n· ª A· èqª * a0 ∞ + ∑ ( an cos nx + bn sin nx) 2 n =1 n =1 a0 = aA0x a n = An sin ϕ nx bn = An cos ϕ nx ωt = xx 1, sin x, cos x, sin 2 x, cos 2 x sin nx, cos nx À k 0x a0 ∞ + ∑ ( an cos nx + bn sin nx)x 2 n =1 x [−π ,π ] ∞ f ( x) = = 2π x π 1 an = ∫ f ( x ) cos nxdxx π −π π b = 1 f ( x)sinnxdxx n π∫ −π (n = 0,1,2) ( n = 1,2,3) 11 π2 1+ 2 + 2 + = 8 35 x 1 1 1 π2 + + + = 22 42 62 24 ÷· ¸nª ÷· ¸nª ±µ U 2l 111 π2 + 2 + 2 + = x 6 22 3 4 111 π2 1− 2 + 2 − 2 + = x 234 12 1+ π 2 a n = 0x bn = ∫ f ( x) sin nxdxx π0 bn = 0x an = 2 f ( x) cos nxdxx π∫ 0 π n = 1,2,3 x f ( x) = ∑ bn sin nxx n = 0,1,2 x f ( x ) = a0 + ∑ an cos nxx 2 f ( x) = a0 ∞ nπx nπx + ∑ (an cos + bn sin ) 2 n =1 l l = 2l l 1 nπx an = ∫ f ( x) cos dx (n = 0,1,2) l −l l l b = 1 f ( x ) sin nπx dx ( n = 1,2,3) n l∫ l −l € 3 v( ª L·* ¨ 3 y ′ = f ( x, y ) ¨ 3 P ( x, y )dx + Q( x, y ) dy = 0 g ( y )dy = f ( x)dx( v L·* ª G ( y ) = F ( x ) + C( v L·* ª dy = f ( x, y ) = ϕ ( x , y ) dx du dx du u+ = ϕ (u ) ∴ = ¨ dx x ϕ (u ) − u y v( ª L·* x y x u ∫ g ( y)dy =∫ f ( x)dx ¨ 3 u= ¨ À v( ª L· y x dy du =u+x dx dx ¨1 3 x Q( x ) = 0x , Q ª v·* L x Q( x )¨≠ 0 2Q v·* ª L L Øv·* ª dy + P ( x ) y = Q( x) dx − P ( x ) dx y = Ce ∫ y = ( ∫ Q ( x )e ∫ P ( x ) dx − P ( x ) dx dx + C )e ∫ dy + P ( x ) y = Q( x) y nx(n ≠ 0,1) dx P ( x, y )dx + Q( x, y )dy¨= 0 3 ª v·* Q L ∂u ∂u = P ( x, y )x = Q( x, y ) ∂x ∂y x x du ( x, y ) = P ( x, y )dx + Q( x, y )dy = 0x ∴ u ( x, y ) = C ¨ 3 ª Mv·* c f ( x) ≡ 0n d2y dy + P( x) + Q( x) y = f ( x)n dx dx 2 f ( x) ≠ 0ª Lv· P M H ‘ª ªµ 84·S * * (*) y ′′ + py ′ + qy = 0x ª v·L Q 1Q ªL v·* 2x (∆)Q ª v·L p, qx r 2x r ¨ 3 (*)x y ′′, y ′, yx ( ∆) r 2 + pr + q = 0x r1 , r2 3 r1x r2x x K ¸·* ª x¬ K·* ª x÷ K·* ª ø r1 , r2 À ( p 2 − 4q > 0) ( p 2 − 4q = 0) ( p 2 − 4q < 0) p 2 4q − p 2 2 (*)( x E· ª (*)n y = c1e r1x + c2 e r2 x y = (c1 + c2 x)e r1x y = eαx (c1 cos βx + c2 sin βx ) r1 = α + iβ r2 = α − iβ α =− Ð vΗ ª ·* iù E β= y ′′ + py ′ + qy = f ( x) p, q f ( x) = e λx Pm ( x) λx λ f ( x) = e [ Pl ( x ) cos ωx + Pn ( x ) sin ωx] ...
View Full Document

Ask a homework question - tutors are online